World Economic Outlook : September 1984. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1984)
Recent indicators suggest that activity in the world economy is strengthening more rapidly than projected by the staff six months ago. This is especially true of the United States, but the staff has also revised upward its growth projections for most other industrial countries-in the case of Japan and several of the smaller industrial countries by significant amounts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet